Perbedaan Keefektivan Antara Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) dan Tipe Jigsaw Ditinjau dari Hasil Belajar Matematika - Raoda Ismail (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This study is an experimental study that aims to determine the significant difference between the cooperative learning model of the NHT type and the Jigsaw type in terms of student learning outcomes on the surface area and volume of cubes and blocks. The population in this study were all students of class VIII SMP Negeri 4 Jayapura, totaling 184 people and divided into 6 classes. Sampling in this study used a purposive sampling technique, with a sample of 60 people consisting of two classes, namely class VIII C with 30 students and VIII F with 30 students. The design used in the study was a non-equivalent group pretest-posttest design. The analysis used to calculate the hypothesis is the Mann-Whitney test using the SPSS application. The results of the pretest analysis with the Mann-Whitney test obtained a significance value of 0.224. Because the significance value is greater than the 0.05 significance level, it is concluded that the hypothesis H0 is accepted. The results of the posttest analysis with the Mann-Whitney test obtained a significance value of 0.242. Because the significance value is greater than the 0.05 significance level, it is concluded that the hypothesis H0 is accepted. Thus, it can be concluded that there is no significant difference between the learning outcomes of students who are taught using the NHT and Jigsaw cooperative learning models on the surface area and volume of cubes and blocks in class VIII SMP Negeri 4 Jayapura